1993
DOI: 10.3758/bf03334956
|View full text |Cite
|
Sign up to set email alerts
|

Laterality effects in the haptic horizontal-vertical illusion

Abstract: The tactile horizontal-vertical illusion was studied as a function of hand, size, and figure (L or inverted 1'). Independent groups of subjects examined raised-line L and inverted T shapes with their left or right thumbs. The illusion varied with stimulus size and the nature of the figurethat is, with whether the pattern was an inverted T or an L shape. No illusion appeared for the L configuration. Furthermore, the strength of the illusion was linked to stimulus size, with the illusion appearing for larger inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, the methods used are not all that different from those used in other research for the study of illusions (Amazeen & DaSilva, 2005) and have advantages over the use of a fingers posture for size estimates (e.g., Heller et al, 1997;Heller, Joyner, & Dan-Fodio, 1993;Smeets, Brenner, de Grave, & Cuijpers, 2002). The rulers were in different spatial locations than the extents being judged, and conceivably, this could prompt systematic errors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the methods used are not all that different from those used in other research for the study of illusions (Amazeen & DaSilva, 2005) and have advantages over the use of a fingers posture for size estimates (e.g., Heller et al, 1997;Heller, Joyner, & Dan-Fodio, 1993;Smeets, Brenner, de Grave, & Cuijpers, 2002). The rulers were in different spatial locations than the extents being judged, and conceivably, this could prompt systematic errors.…”
Section: Resultsmentioning
confidence: 99%
“…The horizontal^vertical illusion may be stronger with the use of the right hand (Heller et al 1993), since the right brain may be more accurate in the processing of spatial information. Tsai reported a stronger illusion with the use of the right hand, but also found that the Mu« ller-Lyer illusion was present when subjects felt stimuli with their left hands (Tsai 1967 …”
Section: Resultsmentioning
confidence: 99%
“…Study of the illusion is further complicated by the finding that illusory effects were influenced by the hand used to feel the raised-line patterns (Heller, Joyner, & Dan-Fodio, 1993). The illusion was found only for inverted-T figures, and no illusion was found for the left thumb.…”
mentioning
confidence: 99%